Speech intelligibility studies in a historic multipurpose room - Jaramillo, Ana M.; Nelson, Peggy B.; Olson, Bruce C. (The Journal of the Acoustical Society of America, 2017)
The Speech-Language-Hearing Sciences department at the University of Minnesota is located in Shevlin Hall, a historic building dating from the 1920s. Shevlin Hall has a large room on the first floor with a high coffered ceiling that is often used for receptions and presentations but also serves as a classroom. Students with hearing loss often complained about attending classes in Shevlin 110 due to its high reverberation times, combined with window AC unit noise, resulting in very degraded speech intelligibility. In 2013, the room went through renovations that addressed room acoustics, sound system design, as well as lighting and equipment (not including AC). Post-renovation measurements and subjective impressions have shown a significant improvement in speech intelligibility in the room. For this paper, we are looking at subject-based intelligibility tests to compare with prediction metrics and simulations, as well as collecting a qualitative narrative on the department’s impression on the room before and after renovations.